Pemanfaatan Batu Sungai Pappa Kecamatan Polong Bangkeng Utara, Kabupaten Takalar Dalam Campuran AC - WC - Nari Ro'son; Rais Rachman; Alpius (Paulus Civil Engineering Journal, 2023)
Road infrastructure development is very necessary to improve the main sectors in moving the wheels of the national and regional economy. Given the importance of road infrastructure development, it becomes necessary to find alternative solutions by utilizing available natural resources for the development of basic materials for road pavement. This study aims to utilize Batu Sungai Pappa, North Bangkeng Pod District, Takalar Regency in a mixture of air conditioning – toilets. The method used in this study was to first design the composition of the AC – WC mixture, carry out a series of coarse, fine and filler aggregate tests, then use the Marshall test to determine the properties of the mixture and the Marshall immersion test to determine the Marshall stability of the remaining mixture with the amount of asphalt. The results of research conducted at the Road and Asphalt Laboratory of the Christian University of Indonesia Paulus Makassar, indicate that the characteristics of the pavement material in the form of Kali Pappa Stone, Polong Barkeng Utara District, Takalar Regency fulfill the requirements as a material for making pavement layers. Through the Marshall test, the characteristics of the AC – WC mixture were obtained with asphalt content of 5.50%, 6.00%, 6.50%, 7.00%, 7.50%. The test results of Marshall Immersion mixture of AC – WC with an optimum asphalt content of 5.50% obtained Residual Marshall Stability of 94.36% meeting the 2018 Bina Marga Specifications, which is at least 90%.